Model Inovasi Penggalian Sumber Pendapatan Non-Akademik dalam Mendukung Kemandirian Keuangan PTKIN Badan Layanan Umum - Nurul Setianingrum; Fatimatuzzahro; Risanda A. Budiantoro (Al-Musthofa: Journal of Sharia Economics, 2026)
This study aims to analyze the management of non-academic revenue sources in State Islamic Higher Education Institutions with Public Service Agency status (PTKIN BLU), identify the challenges and opportunities for their development, and formulate a sustainable revenue innovation model. This research employed a qualitative approach using field research methods through in-depth interviews, observations, and documentation studies. The objectives of this study are to analyze the management and exploration of non-academic revenue sources in PTKIN BLU, identify challenges and opportunities in optimizing non-academic revenue sources, and identify innovation models that can be developed to sustainably increase non-academic revenue in PTKIN BLU. The findings indicate that the management of non-academic revenue has evolved toward a more professional and adaptive governance system, although it still faces institutional, human resource, and financial digitalization challenges. This study proposes the Integration and Accountability Model (I²A), which consists of structural innovation through strengthening business unit governance, collaborative innovation through strategic partnerships with industries and Islamic financial institutions, and sustainable innovation oriented toward economic, social, and spiritual sustainability to support the financial independence of PTKIN BLU based on transparency and Islamic values.